New model of the sedimentation process of polydisperse post-coagulation suspension - Mariusz Rząsa; Ewelina Łukasiewicz (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
Coagulation is a process during which a flocculent suspension may sediment. It is characterized by its polydisperse structure. There are three main fractions of sedimentation particles after coagulation: spherical, non-spherical and porous agglomerates. Each of the fractions sediments in a different manner, for different forces act on them, due to interactions between the particles, inhibition or entrainment of neighboring particles. The existing sedimentation models of polydisperse suspension do not consider the flocculation process, i.e. the change of one particle into another during sedimentation, resulting from their agglomeration. The presented model considers the shape of particles and flocculation, which is a new approach to the description of the mathematical process of sedimentation. The velocity of sedimentation depends on the concentration of particles of a given fraction in a specific time step. Following the time step, the heights of individual fractions are calculated. Subsequently, new concentration values of individual fractions are determined for the correspondingly reduced volume of occurrence of a given fraction in the volume analyzed, taking particle flocculation into consideration. The new concentration values obtained in this way allow to recalculate the total sedimentation rates for the next time step. Subsequent iterations allow for numerical simulation of the sedimentation process.